Effect of stretching exercises on blood gluocse levels in patients with type 2 diabetes mellitus: a brief review - Manisha Tanwar; Sikka, Gitanjali; Jain, Deepak (International Journal of Research in Medical Sciences, 2023)
Diabetes has become worldwide pandemic. Among the diabetic population 90-95% patients have type 2 diabetes mellitus (T2DM). The development of T2DM can be slowed down by modification in lifestyle through physical activities such as brisk walking, physical body movement and adopting proper balanced diet. Various physical exercises such as aerobic exercises, resistance exercises, high intensity interval training performed regularly can help with management of blood glucose level, lipid profile, blood pressure, quality of life and cardiovascular complications. Geriatric patients with type 2 diabetes are either extremely frail, wheelchair bound, or bed bound and do not have sufficient physical work capacity to exercise aerobically and with high resistance. Static stretching of the skeletal muscles accrues the benefits of exercise without its accompanying physical stress as in case of aerobic exercise and resisted exercises. Several studies have shown that stretching helps in lowering the blood glucose level in patients with T2DM immediately after the intervention. Till date there are no definitive guidelines are present for stretching exercises as treatment protocol for reduction of blood glucose level and HbA1c level in patients with T2DM. In order to establish a definitive stretching protocol in patients with T2DM and for individual based exercise to be decided further research needs to be conducted.